Differences in morphological characteristics and body composition between of two elite volleyball players in Montenegro - Bojanic, D.; Ljubojevic, M.; Krivokapic, D.; Nokic, A.; Tabakovic, M. (Journal of Physical Education and Sport, 2020)
Contemporary volleyball is a very popular sport, as some kind of recreational activity, but also as a professional sport which is played by a very large part of both male and female population. The aim of this research was to determine the differences related to morphological characteristics and body composition among two top volleyball players in Montenegro participants of the Cup Finals 2018-19. The sample of 29 subjects was divided into two sub-samples, the sub-sample of the subjects consisting of 12 players of VC Budva, of the average age 26.23±4.2, the champions of Montenegro 2018-19, the other sub-sample of 17 players of VC Buducnost, of the average age 18.19±1.4, the participant in the European Challenge Cup 2018-19. Anthropometric characteristics in the body composition were evaluated by a battery of 11 variables: body height (cm), body weight (kg), triceps skinfold (mm), skinfold of the back, biceps skinfold, abdominal skinfold, thigh skinfold, calf skinfold, body mass index (BMI), percentage of fat (%) and muscle mass (kg). Statistically significant differences (p<0.05) between body composition and anthropometric characteristics of the top two volleyball clubs, was determined by using a discriminatory parametric procedure with a t-test for small independent samples. The results showed that the volleyball players of the two mentioned clubs have statistically significant differences by the four variables that estimate the triceps skinfold, calf skinfold, thigh skinfold, and muscle mass, in favor of VC Budva. These results could be helpful to the other coaches and clubs in Montenegro, dealing with the selection and planning of the training process.